2003
DOI: 10.1097/01.ju.0000060882.75475.5a
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis and Description of Smr1 Gene in Rat Penis in a Post-Radical Prostatectomy Model of Erectile Dysfunction

Abstract: Impressive and previously unrecognized genetic changes are being intensely investigated as they are being unmasked by GeneChip technology. We have identified and begun the investigation of 1 interesting family of genes, namely submandibular gland proteins. The role of SMR as a clinically relevant change in penile and/or urethral function following cavernous nerve injury is speculative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
5
24
0
Order By: Relevance
“…Diabetes is a risk factor for both CVD and ED, and we have previously reported that in diabetic patients and diabetic animal models the genes encoding opiorphin-related products are downregulated in CSM tissue (1,(42)(43)(44)46). In the present study, we demonstrate that experimental diabetes is also associated with reduced Vcsa1 gene expression in other tissues and with significantly lower plasma levels of sialorphin, the rat opiorphin homologue.…”
Section: Discussionsupporting
confidence: 63%
“…Diabetes is a risk factor for both CVD and ED, and we have previously reported that in diabetic patients and diabetic animal models the genes encoding opiorphin-related products are downregulated in CSM tissue (1,(42)(43)(44)46). In the present study, we demonstrate that experimental diabetes is also associated with reduced Vcsa1 gene expression in other tissues and with significantly lower plasma levels of sialorphin, the rat opiorphin homologue.…”
Section: Discussionsupporting
confidence: 63%
“…17 Micro array analysis showed a diversity of RNA expression in penile tissue. 18 Similar protein expression was observed in vascular smooth muscle. 19,20 These results imply that the protein composition in rat penile corpus cavernosum shows to have similar pattern of expression to other tissues 19 and that these proteins may participate in the physiological and pathological functions of penis.…”
Section: Characters Of Protein Expression In Penile Tissuesupporting
confidence: 60%
“…9 It has been reported that CNR induced various responses in penile corpus cavernosum including apoptosis. 18 CNR model showed several changes in functional and molecular aspects, 18 the functional characteristics, however, were not fully defined. In this study, we found that RhoGDI content was increased in penile corpus cavernosum form CNR rats compared with sham-operated rats, which was confirmed with Western blot analysis.…”
Section: Changes Of Rhogdi Protein During Cnrmentioning
confidence: 99%
“…Vcsa1 was up-regulated with each treatment (tables 1 and 2). This is of particular interest since Vcsa1 has been suggested as a marker of ED because it is down-regulated in several animal models of ED 3,12. Neither microarray analysis nor quantitative RT-PCR revealed significant changes in Slo gene expression (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Vcsa1 , one of the genes changed as a physiological response to the recovery of erectile function, has previously been suggested to be a marker of ED in several animal models 3,12. We determined whether Vcsa1 expression correlated with the recovery of erectile function after the administration of the PDE5 inhibitor tadalafil alone or in association with pVAX-hSlo.…”
Section: Resultsmentioning
confidence: 99%